A study of police personnel wellbeing in England and Wales whilst working during the Covid-19 pandemic - Roach, Jason (Policing and society, 2025)
This paper presents the findings of a mixed-method study exploring the self-reported negative impact on wellbeing of working in policing in England and Wales during the Covid-19 pandemic. For the first time, findings relating to the wellbeing of UK police and police staff are presented from two different points in time during the pandemic period – the initial ‘lockdown phase’ (March 2020) and Autumn 2021 as the UK began to return to pre-pandemic social behaviours. A first study presents data collected via electronic survey, completed in June 2021 by more than 500 UK police officers and staff, exploring how they felt initially about the Covid-19 pandemic and how they felt later in 2021. For example, how it affected their work and how they dealt with the changes in working practices. A second study presents an Interpretive Phenomenological Analysis of 18 interviews capturing the individual ‘life experiences’ of UK police officers and staff working in variety of policing roles during the pandemic. Key themes identified include the negative effects of working at home and the worry of spreading the disease to loved ones. Recommendations are made for how police forces can better support the wellbeing of officers and staff during pandemic scenarios and increase resilience. For example, by quickly identifying those officers and staff most vulnerable to the disease and/or most anxious generally at the start of a pandemic, to plan for how appropriate support can be provided, and acknowledge that police staff feel most isolated when working from home.